Judicial Oversight on Administrative Decisions in Afghanistan - Najibullah Faiez (Administrative and Environmental Law Review, 2022)
Public authorities have taken administrative decisions. Here in Afghanistan, administrative laws are unwritten and lack proper mechanisms for judicial oversight due to the instability of four decades of war. This article, titled “Judicial Oversight on Administrative Decisions in Afghanistan”, tries to study administrative decisions in Afghanistan and seeks to provide a special mechanism for judicial oversight of administrative decisions. The article has answered the question: what are administrative decisions and its judicial oversight? It is a qualitative research conducted through the desk review method and has used an interview with academics specialists in Administrative law. This article also studied other countries' solutions for their judicial oversight.  The result of the research is judicial oversight on administrative decisions in Afghanistan does not have an appropriate mechanism and Afghanistan cannot create an administrative court like France's model. Afghanistan needs to reform judicial power to solve the administrative dispute excellently. Enacting Administrative Procedural law for administrative divan is an urgent task for Afghanistan. This law must abridge the investigation procedure, lower court expenses and increase the court accessibility to citizens to amplify the rule of law.